Recent Advances in 2D Heterostructures as Advanced Electrode Materials for Potassium‐Ion Batteries. Issue 3 (1st February 2022) - Dong, Yulian; Yan, Chengzhan; Zhao, Huaping; Lei, Yong
Abstract : Owing to the cost‐effectiveness, Earth abundance, and suitable redox potential, potassium‐ion batteries (PIBs) stand out as one of the best candidates for large‐scale energy storage systems. However, the large radius of K + and the unsatisfied specific capacity are the main challenges for their commercial applications. To address these challenges, constructing heterostructures by selecting and integrating 2D materials as host and other materials as guest are proposed as an emerging strategy to obtain electrode materials with high capacity and long lifespan, thus improving the energy storage capability of PIBs. Recently, numerous studies are devoted to developing 2D‐based heterostructures as electrode materials for PIBs, and significant progress is achieved. However, there is a lack of a review article for systematically summarizing the recent advances and profoundly understanding the relationship between heterostructure electrodes and their performance. In this sense, it is essential to outline the promising advanced features, to summarize the electrochemical properties and performances, and to discuss future research focuses about 2D‐based heterostructures in PIBs. Abstract : Constructing 2D heterostructures plays a critical role in addressing the challenges of 2D materials as advanced electrode materials for improving the performance of potassium‐ion batteries. A comprehensive overview is given on recent advances in developing 2D heterostructures for potassium‐ion batteries. By thoroughly discussing the advantages and disadvantages of various 2D heterostructures, a perspective on future opportunities is presented.